A Scope of Islamic Business Economics Fiqh: Analysis of Research Trends Through Bibliometrics and Systematic Literature Review - Mayang Sari, Junia (al-Uqud : Journal of Islamic Economics, 2026)
The decline in Islamic economic jurisprudence has led to broader discussions on the scope of Islamic business economics jurisprudence. Addressing this issue can build a scientific framework from several perspectives, as Muslim scholars have made many developments in Islamic business economics jurisprudence within the scope of analysis. Discussion of the scope of Islamic business economics jurisprudence. However, literature on Islamic business economics jurisprudence specifically is still very limited in its focus on this area. Other studies have focused on specific objects within Islamic business economics jurisprudence. This study uses bibliometric methods and a systematic literature review (SLR) to obtain a broader and deeper picture of the development of Islamic business economics jurisprudence studies and research trends in raising this study. In this case, the literature collected came from the Scopus database using Publish or Perish software and a Scopus account. The results show that the trend of Islamic business economics studies has increased, indicating that for about a decade, the topic of Islamic business economics research has been a favorite among researchers in the field of economics. The results of mapping with Vosviewer and a review of selected journals show that the future scope of Islamic economics studies is based on publication trends in the development of Islamic financial systems, factors in economics, the development of sharia insurance, and contemporary Islamic business economics practices.